Formal Methods in Systems Biology First International Workshop, FMSB 2008, Cambridge, UK, June 4-5, 2008, Proceedings - Fisher, Jasmin (Lecture Notes in Bioinformatics, 2008)
This book constitutes the refereed proceedings of the First International Workshop on Formal Methods in Systems Biology, FMSB 2008, held in Cambridge, UK, in June, 2008. The 9 revised full papers presented were carefully reviewed and selected from the workshop lectures that all were invited contributions. The purpose of this meeting was to identify techniques for the specification, development and verification of biological models. It also focused on the design of tools to execute and analyze biological models that can significantly advance our understanding of biological systems.